Qualitative properties of solutions to a nonlinear transmission problem for an elastic Bresse beam - Fastovska, Tamara; Langemann, Dirk; Ryzhkova, Iryna (Frontiers in Applied Mathematics and Statistics, 2024)
We consider a nonlinear transmission problem for a Bresse beam, which consists of two parts, damped and undamped. The mechanical damping in the damping part is present in the shear angle equation only, and the damped part may be of arbitrary positive length. We prove the well-posedness of the corresponding system in energy space and establish the existence of a regular global attractor under certain conditions on the nonlinearities and coefficients of the damped part only. Besides, we study the singular limits of the problem under consideration when curvature tends to zero, or curvature tends to zero, and simultaneously shear moduli tend to infinity and perform numerical modeling for these processes.